New frontiers in acute stroke management - Pushpendra Nath Renjen; Shivangi Garg; Anjali Mishra; Dinesh Mohan Chaudhari (Apollo Medicine)
Ischemic stroke is a common emergency presentation to hospital with improving survival rates owing to access to specialist organized stroke care. The approach to the treatment of ischemic stroke has undergone great transformation over the past 20 years. The negativism of older times has given the way to proven treatment strategies to reverse ischemia and prevent patients from severe neurological disabilities or death. Acute stroke care has three main ideologies: (1) timely achievement of occluded artery recanalization and reperfusion of the part of brain that is ischemic, (2) optimization of collateral flow, and (3) avoidance of the secondary brain injury. In this review article, we will focus on the new developments in the management of acute stroke in the past decade.